2019
DOI: 10.1002/bies.201900002
|View full text |Cite
|
Sign up to set email alerts
|

When Cultures Meet: The Landscape of “Social” Interactions between the Host and Its Indigenous Microbes

Abstract: Animals exist as biodiverse composite organisms that include microbial residents, eukaryotic cells, and organs that collectively form a human being. Through an interdependent relationship and an inherent ability to transmit and reciprocate stimuli in a bidirectional way, a human body or the holobiont secures growth, health, and reproduction. As such, the survival of a holobiont is dependent on the maintenance of biological order including metabolic homeostasis by tight regulation of the communication between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…152,153 The normal skin microbiome has adapted to a relatively nutrient poor and acidic environment and is a crucial part of the skin's outermost barrier, preventing infection through competition and antimicrobial mechanisms. [154][155][156] Despite the frequent use of antimicrobial therapy in HS, little was known about patient skin and gut microbiomes until quite recently. 153 Recent studies regarding the HS skin and gut microbiomes have been extensively reviewed elsewhere, but there are a few key considerations which we will reflect on here for future research.…”
Section: The S K In Microb I Ome " Barrier " In Hsmentioning
confidence: 99%
“…152,153 The normal skin microbiome has adapted to a relatively nutrient poor and acidic environment and is a crucial part of the skin's outermost barrier, preventing infection through competition and antimicrobial mechanisms. [154][155][156] Despite the frequent use of antimicrobial therapy in HS, little was known about patient skin and gut microbiomes until quite recently. 153 Recent studies regarding the HS skin and gut microbiomes have been extensively reviewed elsewhere, but there are a few key considerations which we will reflect on here for future research.…”
Section: The S K In Microb I Ome " Barrier " In Hsmentioning
confidence: 99%
“…Hosts, in turn, influence microbial composition and, by extension, metaorganism nervous function, through diet, stress, social interactions, exercise, immune function, antibiotics, birth mode and rearing practices (see Geva‐Zatorsky et al for further examination of the microbiome and early life programming), and even genetic composition . As such, the gut microbiota–brain axis represents a continued, bidirectional dialogue between what was traditionally considered solely the (human) “self” and (microbial) “non‐self”—a dialogue from which the metaorganism emerges as a shared field with a dynamic of its own, an integrated functionality to which neither humans nor microbes are reducible.…”
Section: The Microbiota Expands Nervous Function Beyond the Brainmentioning
confidence: 99%
“…Bosch et al suggest that new knowledge of the diversity of host–microbe interactions found across the animal kingdom will provide new insights into how animals develop, evolve, and manifest disease. Geva‐Zatorsky et al present an overview and a perspective on the social, molecular, and health‐related interactions that humans have with their microbial residents. In an essay written by a biological anthropologist, an anthropologist‐historian, and a clinical scientist, Amato et al construct the human microbiome through evolution by discussing how changes in host diet, environment, and physiology have altered microbial community composition and functions, and consequently, their effect on human disease and health.…”
mentioning
confidence: 99%